2020
DOI: 10.7150/ijbs.38722
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD83 alleviates experimental allergic rhinitis through modulating antigen-specific Th2 cell property

Abstract: Background and aims: Dysfunction of the immune regulatory system plays a role in the pathogenesis of allergic rhinitis (AR). The underlying mechanism needs to be further investigated.Published data indicate that soluble CD83 (sCD83) has immune regulatory activities. This study aims to investigate the role of sCD83 in the alleviation of experimental AR. Methods: Peripheral blood samples were obtained from AR patients. Serum levels of sCD83 were determined by enzyme-linked immunosorbent assay. A murine AR model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…A very recent study brought up a new view on the mode of action of sCD83 in the regulatory network of immune responses: by binding to CD154 on Th2 cells, sCD83 represses the apoptotic inhibitor Bcl2L12, thereby promoting cell death of this particular T cell subset (70). As a corollary, administration of sCD83 to animals with allergic rhinitis (AR) alleviated disease symptoms by restricting the Th2 response.…”
Section: Cd83 Binding Partners and Signaling Cascadesmentioning
confidence: 99%
“…A very recent study brought up a new view on the mode of action of sCD83 in the regulatory network of immune responses: by binding to CD154 on Th2 cells, sCD83 represses the apoptotic inhibitor Bcl2L12, thereby promoting cell death of this particular T cell subset (70). As a corollary, administration of sCD83 to animals with allergic rhinitis (AR) alleviated disease symptoms by restricting the Th2 response.…”
Section: Cd83 Binding Partners and Signaling Cascadesmentioning
confidence: 99%
“…It has been found that soluble CD83 (sCD83) had immune regulatory functions [20]. Our recent publications show that sCD83 suppresses Th2 response [21]. Royzman et al [10] found that administration of sCD83 could inhibit rheumatoid arthritis in an sCD83/indoleamine-2, 3-dioxygenase/TGF-β-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The above information suggests that epithelial cell‐derived factors may involve immune tolerance establishment by Treg generation in the airway mucosa. Our recent work shows that CD83 can suppress antigen‐specific Th2 response in the nasal mucosa 16 . Others found that CD83 attenuates autoimmune disorders 17 .…”
Section: Introductionmentioning
confidence: 91%
“…Our recent work shows that CD83 can suppress antigenspecific Th2 response in the nasal mucosa. 16 Others found that CD83 attenuates autoimmune disorders. 17 CD83 is a member of the immunoglobulin family; it can be produced by B cells and dendritic cells and usually used as a marker of dendritic cells.…”
Section: Introductionmentioning
confidence: 99%